The Italian Deaf Community at the Time of Coronavirus - Tomasuolo, Elena; Gulli, Tiziana; Volterra, Virginia; Fontana, Sabina (Frontiers in Sociology, 2021)
The present paper will explore the impacts of the recent pandemic crisis on the Italian Deaf community, as a linguistic minority. Recent research has shown that minorities are suffering much more the effects of the pandemia because their lack of access to services and in a much wider perspective, to education and welfare. We will show that, during the COVID crisis, despite lockdown measures, various actions at the formal political level (from the Italian Deaf Association) and at the informal level (from the members of the community) promoted sign language and the Deaf community within the hearing majority. In particular, we will analyse how social networks were exploited at the grassroot level in order to promote social cohesion and share information about the coronavirus emergency and how the Deaf community shaped the interpreting services on the public media. The role of social networks, however, has gone far beyond the emergency as it has allowed deaf people to create a new virtual space where it was possible to discuss the appropriateness of various linguistic choices related to the COVID lexicon and to argue about the various interpreting services. Furthermore, in such emergency, the interpreting services were shaped following the needs expressed by the Deaf community with the results of an increased visibility of Italian sign language (LIS) and empowerment of the community. Materials spontaneously produced by members of the Deaf Italian community (conferences, debates, fairy tales, and entertainment games) were selected, as well as materials produced by LIS interpreters committed to guaranteeing access to information. By highlighting the strategies that a minority group put in place to deal with the COVID-19 emergency, we can better understand the peculiarities of that community, creating a bridge between worlds that often travel in parallel for respecting the peculiarities of each other (deaf and hearing communities).